1997
DOI: 10.1073/pnas.94.24.12780
|View full text |Cite
|
Sign up to set email alerts
|

Global variation in the genetic and biochemical basis of diamondback moth resistance to Bacillus thuringiensis

Abstract: Insecticidal proteins from the soil bacterium Bacillus thuringiensis (Bt) are becoming a cornerstone of ecologically sound pest management. However, if pests quickly adapt, the benefits of environmentally benign Bt toxins in sprays and genetically engineered crops will be short-lived. The diamondback moth (Plutella xylostella) is the first insect to evolve resistance to Bt in open-field populations. Here we report that populations from Hawaii and Pennsylvania share a genetic locus at which a recessive mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
4
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(168 citation statements)
references
References 40 publications
8
155
4
1
Order By: Relevance
“…It has previously been reported that resistance to Cry1Ab in F 1 progeny of P. xylostella from the Philippines was influenced by the sex of the resistant parent, but sex linkage was discarded since no significant difference was found in the number of male and female survivors (19). All other studies on P. xylostella, (13,32,34,37), P. interpunctella (20), and H. virescens (11) have indicated autosomal inheritance for resistance to B. thuringiensis and its Cry1 toxins. Another significant feature of the resistance common to the selected subpopulations Cry1Ab-SEL and Cry1Ac-SEL was the multigenic basis of inheritance to Cry1Ab in the Cry1Ab-SEL subpopulation and Cry1Ac in the Cry1Ac-SEL subpopulation (29), even though we cannot discard other genetic alternatives based on a single gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been reported that resistance to Cry1Ab in F 1 progeny of P. xylostella from the Philippines was influenced by the sex of the resistant parent, but sex linkage was discarded since no significant difference was found in the number of male and female survivors (19). All other studies on P. xylostella, (13,32,34,37), P. interpunctella (20), and H. virescens (11) have indicated autosomal inheritance for resistance to B. thuringiensis and its Cry1 toxins. Another significant feature of the resistance common to the selected subpopulations Cry1Ab-SEL and Cry1Ac-SEL was the multigenic basis of inheritance to Cry1Ab in the Cry1Ab-SEL subpopulation and Cry1Ac in the Cry1Ac-SEL subpopulation (29), even though we cannot discard other genetic alternatives based on a single gene.…”
Section: Discussionmentioning
confidence: 99%
“…If two resistant strains are crossed, each with recessive alleles for resistance at separate loci, allelic complementation will restore susceptibility (the wild-type phenotype) in the progeny. However, if the recessive resistance alleles occur at the same locus in different populations, the progeny will be resistant because they will inherit resistance alleles at the same locus from both parents (34).…”
mentioning
confidence: 99%
“…The purpose of the refuge is to maintain a population of the target insects with susceptible alleles to the Cry proteins. The high dose/refuge strategy assumes that development of resistance to Cry proteins by insects is conferred by recessive mutations (Tabashnik et al, 1997) and that the presence of these alleles is rare in insect populations (Andow and Alstad, 1998). On this basis, insects homozygous for resistance alleles will be very rare.…”
Section: Will Gm Crops Lead To Superpests and Superdiseases?mentioning
confidence: 99%
“…However, if the mutations are in different genes then the offspring would be susceptible. Tabashnik et al [18] performed complementation assays on three resistant populations (PEN, NO-QA and PHI) and found that all three shared a common resistance locus. In 2005 it was reported that complementation tests between an artificial diet adapted derivative of NO-QA (NO-QAGE) and an independently isolated resistant population SC1 demonstrated that the same locus was present in SC1 [19].…”
Section: How Many Mutations Cause Resistance In Plutella?mentioning
confidence: 99%